Egg yolk phosphatidylcholine enrichment in unsaturation fatty acids: Extraction and molecular structure - ZHU Shuai; HUANG Meng-ling; FAN Li; YANG Rui-peng; ZHANG Min; LIU Yun (Liang you shipin ke-ji, 2020)
Egg yolk is rich in phosphatidylcholine (PC), which is the keyphospholipid component providing nourishment and protection for our body. We herein optimize the ethanol extraction parameters for PC in egg yolk using response surface methodology. After preliminary purification through thin-layer chromatography, PCfatty acid compositions are identified by gas chromatography-mass spectroscopy (GC-MS), and their molecular structure are also elucidated by matrix-assisted laser desorption ionization time-of-flight mass spectroscope (MALDI- TOF/MS). Results show that the optimal parameters for PC extraction from egg yolk are: weight/volume ratio of egg yolk to ethanol of 1∶16 (g:mL), ethanol concentration of 93.77%, extraction temperature of 42.98 ℃. Under the optimal conditions, 24.38% of PC yield is obtained, and PC content is approx.61.19% detected by UV-Vis spectroscopy. GC-MS analysis reveals that the main fatty acids of PC are oleic acid (40.66%), palmitic acid (16.35%), linoleic acid (13.06%), stearic acid (7.27%), palmitoleic acid (5.19%) and a small amount ofarachidonic acid (0.48%) and docosahexaenoic acid (0.37%). Nine kinds of PC molecular structures are elucidated from MALDI-TOF/MS profiles, namely, 16:0/18:0-PC, 16:0/18:1Δ9-PC,18:0/18:1Δ9-PC, 16:0/18:2Δ9,12-PC, 18:0/18:2Δ9,12-PC, 18:1Δ9/18:2Δ9,12-PC, 16:0/20:4Δ5,8,11,14-PC, 18:0/20:4Δ5,8,11,14- PC and 16:0/22:6Δ3,6,9,12,15,18-PC.